A comparative visual and typological analysis of ancestral houses in Taal, Batangas and Balingasag, Misamis Oriental - Duque, Brenah V. (2019)
Philippines is known for its diverse culture, shaped by geographic conditions, cultural and political influence, that reflects the architectural identity of the country. The popularized Philippine dwelling is the bahay kubo, in which several variations were made by different ethnolinguistic groups, and Spanish and American colonizers which developed the bahay na bato from the Spaniards and tsalet from the Americans. The study focused on how geographical and colonial influence developed the architectural identity of ancestral houses, in terms of architectural elements and spatial layout, in Taal, Batangas and Balingasag, Misamis Oriental and whether there are similarities and differences in its identity. Photo documentation of architectural elements and interview on the spatial layout of the ancestral houses were conducted. Most of the ancestral houses in Taal recorded in the study were built during the Spanish and American colonial period while most of the recorded ancestral houses in Balingasag were built during the American colonial period and mid-twentieth century. The incorporation of some of the architectural elements to the design of the ancestral houses from the Spanish colonial period to the American colonial period gradually declines that by the mid-twentieth century, after the World War II, these elements are considered uncommon on the design of the houses constructed in this period. The planning of the ancestral houses in Taal and Balingasag changed on terms of the location of the staircase, leading to the second floor where spaces such as living room, dining room, kitchen and bedrooms are found, the adjacency of these spaces to one another, and addition of two bedrooms which was two or three bedrooms during the Spanish colonial period. The development of the architectural elements and planning on the design of the ancestral houses in Taal and Balingasag is similar in terms of the recurrence of certain styles of elements and disappearance of some architectural elements, and the arrangement of spaces in the second floor of the houses where the owners live.